Mengamankan Transaksi di Internet: Suatu Tinjauan Terhadap Justifikasi dan Metode - Cahyadi, Adi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2004)
Securing internet transaction has become more crucial considering the rise of cyber crime. Although many business owners have become aware of this, the implementation of security technology especially in developing countries is still somewhat slow and this is not apart from the fact that securing electronic transaction is costly. Improper consulting practice has also resulted in an overspending of budget for security projects. This article tries to shed some light to its readers and business owners on the proper practice of evaluating a security investment, selecting an appropriate security solution as well as introducing major methods of securing an electronic transaction.